Efficient recovery of Fe (III) from dechroming sludge with a novel combined process of acidic leaching and on-line adsorption - Chengbin Zhong; Junxia Yu; Boxi Wu; Qingbiao Zhao; Kairui Zhou; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; Xiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

Marine oil film detection method based on growing hierarchical neural gas network and multi-scale threshold segmentation - Baozhu Jia; Zekun Guo; Jin Xu; Bo Li; Yuanyuan Huang; Min Cheng; Bo Xu; Boxi Yao; Peng Liu (Marine Pollution Bulletin, 2026)

Efficient recovery of chromium from electroplating sludge by a two-step roasting process: Mechanisms and kinetics - Chengbin Zhong; Junxia Yu; Boxi Wu; Jia Wang; Li Guo; Ruan Chi; Zhen Luo; YingYing Liu (Minerals Engineering, 2026)

Photo-responsive imprinted adsorbent based on TiO2 modified porous carbon microspheres to promote selective adsorption and recovery of phenol - Min Zhang; Lei Qin; Boxi Jing; Yuejiao Li; Weifeng Liu; Yongzhen Yang; Xuguang Liu (Journal of Environmental Chemical Engineering, 2025)

Marine radar-based oil spill detection method utilizing particle swarm optimization algorithm - Jin Xu; Boxi Yao; Bo Li; Lilin Chu; Sihan Qian; Bo Xu; Zheng Li; Peng Liu (International Journal of Remote Sensing, 2025)

Synergistic Mn-doping and MXene coupling in sulfur-deficient In2S3 nanosheets for high-performance sodium-ion batteries - Manman Zhang; Qi An; Haocun Ba; Boxi Wang; Beibei Li; Chengjiang Deng; Liuyuan Ma; Yinghong Lan; Xiaoyan Han; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Temperature characteristics reveal the dynamic pattern of isomorphic generation alternation in the environmental adaptation and invasive potential of the green macroalga, Chaetomorpha valida - Bingxin Huang; Liming Rao; Yunyan Deng; Boxi Li; Yanguang Zhong; Chang Sun; Meina Chen; Yuan Gao; Lanping Ding (Acta Oceanologica Sinica, 2025)

Research on Operational Risk for Northwest Passage Cruise Ships Using POLARIS - Long Ma; Jiemin Fan; Xiaoguang Mou; Sihan Qian; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
In the context of global warming, polar tourism is developing rapidly, and the demand for polar cruise travel in the Northwest Passage continues to increase, while sea ice has long been a key factor limiting the development of polar cruise tourism. This study focuses on the operational risk of sea ice on cruise ships in the Northwest Passage (NWP), aiming to provide a scientific basis for ensuring the safety of cruise ship navigation and promoting the sustainable development of polar tourism. Based on ice data from 2015 to 2024, this study used the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology recommended by the International Maritime Organization (IMO) to establish three scenarios for the route of ice class IC cruise ships: light ice, normal ice, and heavy ice. The navigable windows were systematically analyzed and critical waters along the route were identified. The results indicate that the navigable windows for IC ice-class cruise ships under light ice conditions are from mid-July to early December, while the navigable period under normal ice conditions is only from mid- to late September, and navigation is not possible under heavy ice conditions. The study identified Larsen Sound, Barrow Strait, Bellot Strait and Eastern Beaufort Sea as critical waters on the NWP cruise route. Among them, Larsen Sound and Eastern Beaufort Sea have a more prominent impact on voyage scheduling because their navigation weeks overlap less with other waters. This study provides a new idea for the risk assessment of polar cruise ships in ice regions. The research results can provide an important reference for the safe operation of polar cruise ships in the NWP and the decision-making of relevant parties.

Comparative Research on Vessel Navigability on the Northern Sea Route Based on the NSR Admission Criteria and POLARIS Methodology - Long Ma; Sihan Qian; Xiaoguang Mou; Jiemin Fan; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
At present, sea ice remains a critical factor affecting the safety of vessel operations along the Northern Sea Route (NSR). However, inconsistencies between the navigability outcomes derived from the criteria for the admission of ships in the area of the Northern Sea Route (NSR criteria) and the polar operational limit assessment risk indexing system (POLARIS) methodology present challenges for navigational decision-making. This study aims to conduct a systematic comparison of the POLARIS methodology and the NSR criteria in evaluating the navigability of independently operating vessels classified as Arc4 to Arc9. Through comparative calculations of navigability and the navigability rates for six ice-class vessels across 27 districts using the two methods, this study reveals the consistencies and discrepancies in their navigability outcomes. Firstly, using the POLARIS methodology, the risk index outcome (RIO) is calculated for six ice-class vessels across 27 districts. For these districts, the navigability threshold is defined when 95% or more of the area exhibits an RIO greater than or equal to zero. Secondly, using the NSR criteria, navigability ratios for six ice-class vessels under varying ice conditions are evaluated. A navigability threshold is defined when 95% or more of the ice conditions in a district are classified as navigable. Finally, a quantitative comparison of the weekly navigability ratios obtained by the two methods is conducted to reveal the consistencies and discrepancies in the navigability outcomes of each ice-class vessel across different NSR districts. The results indicate that the consistency between the navigability outcomes of the two methods decreases with lower vessel ice classes, particularly in September and March. In general, the consistency of performance between the two methods in terms of navigability outcomes deteriorates as the vessel ice class decreases and ice conditions become more complex. This study provides a scientific foundation and data-based support for route planning and real-time decision-making in polar waters.

Photosynthetic physiology and stress-resistant biochemical properties reveal the invasive photo-adaptation strategy of marine green alga Codium fragile - Bingxin Huang; Boxi Li; Xulei Wang; Liming Rao; Jie Chen; Yang Dai; Lichun Wang; Zhiying Wang; Lanping Ding (Acta Oceanologica Sinica, 2025)

Perfluorodecanoic acid induces the increase of innate cells in zebrafish embryos by upregulating oxidative stress levels - Juhua Xiao; Dou Yang; Boxi Hu; Wenwen Zha; Weirong Li; Ying Wang; Fasheng Liu; Xinjun Liao; Huimin Li; Qiang Tao; Shouhua Zhang; Zigang Cao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Unraveling dynamics and interactions of core microorganisms in the biodegradation of keratin-based feather wastes - Boxi Wang; Yuan Chen; Jin Chuan Wu; Qingxin Li (Journal of Environmental Management, 2024)

Individual differences determine the morphogenesis pattern and reproductive uniqueness of the invasive green macroalga, Chaetomorpha valida, with possible implications for its habitat adaptation - Bingxin Huang; Liming Rao; Yunyan Deng; Boxi Li; Zhiying Wang; Jie Chen; Lichun Wang; Yang Dai; Lanping Ding (Journal of Oceanology and Limnology, 2024)

Montmorillonite-coupled microbially induced carbonate precipitation (MICP) enhanced contaminant removal and carbon capture in cyanide tailings - Yaoting Duan; Lei Niu; Boxi Li; Yang He; Xin Xu; Caiqi Yu; Zhe Wang; Chunqiao Xiao; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2024)

Long-term hourly air quality data bridging of neighboring sites using automated machine learning: A case study in the Greater Bay area of China - Boxi Wu; Cheng Wu; Yuchen Ye; Chenglei Pei; Tao Deng; Yong Jie Li; Xingcheng Lu; Lei Wang; Bin Hu; Mei Li; Dui Wu (Atmospheric Environment, 2024)